2019
DOI: 10.2340/00015555-3273
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerance of Sirolimus (Rapamycin) for Extracranial Arteriovenous Malformations in Children and Adults

Abstract: Managing extracranial arteriovenous malformations is challenging. Sirolimus (rapamycin) is increasingly being used in all kinds of vascular anomalies. In this study, we report the largest series of arteriovenous malformations treated with sirolimus, which included 10 patients (7 children). Results suggest a poor efficacy of sirolimus for this condition, with only partial response in 50% of patients, which was transient and lasted several months in 2 of 5 patients, with further worsening. Managing extracranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…Treatment with sirolimus did not result in resolution in our study, as evident by persistent flow in the AVM. This is in line with the findings of other studies which showed none or only minor improvements at best with the use of sirolimus for AVMs [21,22]. However, it should be considered as a palliative treatment option for management of symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Treatment with sirolimus did not result in resolution in our study, as evident by persistent flow in the AVM. This is in line with the findings of other studies which showed none or only minor improvements at best with the use of sirolimus for AVMs [21,22]. However, it should be considered as a palliative treatment option for management of symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…From the start of sirolimus treatment, 88.9% of the patients with a high‐flow vascular malformation showed improvement in their baseline symptoms, especially the size of the lesion, and the number of episodes of swelling and bleeding. Similar to results reported in previous studies, the median response time was 2 months 12 . However, some patients in our series took 6 months to respond and based on previous studies, some patients may take up to 1 year to respond 12 .…”
Section: Discussionsupporting
confidence: 90%
“…mTOR inhibitors are recently used alternatives to surgical management of large, superficial AVMs in the pediatric population, with rapamycin being the drug of choice in many published reports [3,6]. To date, our study details the 22nd and 23rd known patients to be treated with an mTOR inhibitor for management of a cranial or facial AVM [6,[11][12][13][14][15][16]. There has been substantial variability in dosing and treatment duration across institutions, with treatment duration ranging from 3 to 24.5 months, with a median treatment duration of 12 months across all reported cases [17,18].…”
Section: Review Of Literaturementioning
confidence: 99%
“…One earlier study suggested rapamycin promoted coagulopathy in patients treated with low-flow AVMs based on correlation with significant decrease in D-dimer levels [25]. However, in a case series of both pediatric and adult patients, it was noted that children developed oral ulcers and oral mucositis following rapamycin treatment for extracranial AVMs [13]. Other authors also reported relatively infrequent and minor complications, such as transient hyperlipidemia and minor opportunistic infection [16].…”
Section: Review Of Literaturementioning
confidence: 99%